OPPORTUNITIES FOR USING DIGITAL PAINTING TECHNOLOGIES IN DEVELOPING AESTHETIC TASTE - Ismatova Mashhura Olimjon qizi, (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
This article explores the potential of digital painting technologies in developing aesthetic taste among students. It examines how digital tools such as graphic tablets, drawing software, and interactive applications can enhance creativity, visual perception, and artistic skills. The study highlights the effectiveness of integrating traditional artistic principles with modern digital methods to foster aesthetic sensitivity, composition understanding, and color mastery. Findings indicate that the use of digital painting technologies provides students with versatile opportunities for creative expression, experimentation, and personalized artistic development.